KAJIAN DESALINASI LARUTAN SIMULASI TETES SECARA EKSKLUSI ION - Bundjali, Bunbun
The desalination process is one of the primary stages in the desugarisation of molasses or the manufacturing of liquid sugar from molasses. Desalinated molasses is a more efficient medium for many fermentation processes leading to various products. The desalination process by means of ion exclusion was influenced by various factors, such as the physicochemical nature of the ion exchange resin, the composition of feed and the exclusion column operating variables. In order to obtain optimal desalination, the proper ion exchanger, the optimal volume and composi - tion of feed and suitable.operating conditions should be determined. In this experiment, by using the sodium form of the cation exchanger Dowex 50W X-4 200 - 400 mesh, and the chloride form of the anion exchanger Dowex 1 X-4 50-100 mesh and 100 - 200 mesh, the desalination process of simulated molasses by means of ion exclusion was investigated. For the single pass desalination process, the efficiency of desalination was studied by varying the ratio of length to diameter of ion exchange column. Then the influence of feed volume and salt concentration on the degree of separation were also investigated. To increase the recovery and concentration of the sugar product, the multiplepass process of desalination was also carried out. The influence of the ratio of length to diameter of column on the degree of separation was dependent on the kind of sugar being separated. For the glucose and sucrose solutions, by using the Dowex 50W X-4 - with a flow rate about one mililiter per minute, a temperature of 65Â°C - the most efficient separation was obtained with a ratio of 14.0. On the other hand, for fructose solution, the same operating conditions gave the poorest resolution. For the single pass process, the maximum feed volume which would still give good separation was equal to the interstitial volume in the column packing. This amounted to 2770 of the total volume of the column bed. By using Dowex I X-4, the desalination of feed solutions with salt concentration of 7.39% NaCl or 6.9270 CaC12 still gave a fair resolution. For the molasses simulated solution of 15.58% sucrose and 3.67% NaCl, by using Dowex 1 X-4 resin, four passes - a ratio of length to diameter of column of 6.8, a temperature of 65Â°C, and a flow rate of about one mililiter per minute it was possible to decrease the salt concentration with 7070. The recovered sugar product was about 52.4% with the sugar concentration was 1.3 times that in the initial feed solution.